Management of the Conservative Political Platform of the Transformation Public-power Organization in Eurasia - Baranov, Pavel P.; Mamychev, Alexey Y.; Ovchinnikov, Alexey I. (International Review of Management and Marketing, 2016)
The article examines conservatism as the political thinking style and the transformation strategy of the public-power organization operating at the level of the hidden political discourse in the Eurasian space. The main directions of the conservative evolution of the state and legal organizations in Eurasia, and the public-power system development directions are allocated. Authors prove and characterize opposition between the modernist and Eurasian strategies of the transformation, which qualitatively stimulates transformation of political space in Eurasia. It is reasoned that the transformation processes proceeding in the Eurasian political space are inconsistent and ambiguous therefore for the Eurasian states the convergence socio-political processes combining at the public discourse level – the modernist strategy, and at the hidden discourse level – the conservative orientations in political and economic development. The most obvious result of the transformation process is the transformation of the society basic institutions, the analysis of which shows the disintegration of the socio-economic and political relations. The most susceptible to transformation processes was the government and the public-power organizations. In general, the complexity and contradictions of political processes does not allow to confine any one paradigm in the study. It is therefore advisable selection of basic, conceptual and formulated concepts of political management in the system of political practice. Keywords: modernization and traditionalism, postmodernism, transformation, organization, political management, conservatism JEL Classifications: K49, D71, M11, H55